The elevation gradient of small mammals richness and abundance in the dry Andes of northwestern Argentina. (September 2022) - Urquizo, José H.; Barquez, Rubén M.; Ferro, Ignacio
Abstract: In this research we explore elevation gradient of small mammal diversity on the arid slopes of the Andes in northwestern Argentina. We evaluated the influence of climatic and environmental factors on species richness and abundance across two altitudinal transects between 2700 and 4700 m. We used canonical correspondence analysis, multiple regressions (GLM's), and variation partitioning analysis to evaluate the primary productivity, environmental heterogeneity, and climate as drivers of species diversity. The general trend indicates a greater diversity towards high elevation with an abrupt decrease towards the summit. The most remarkable pattern was the coincident distribution of the maximum values for both, abundance and richness at the same altitude (3700 m). The species richness showed a flattened distribution with the maximum values between 3200 and 3700 m and a small peak at 4200 m. We found that the joint effects of environmental heterogeneity with productivity explained most of the variation for richness and abundance (86.5%, 63.2% respectively). These results highlight the complexity of the mountain environments in desert areas while emphasizing the importance of these habitats for the maintenance of biological diversity. Our results constitute an important tool for the conservation of small mammals diversity in these mountain arid environments. Graphical abstract: Image 1 Highlights: Structured small mammal communities which corresponded with the three ecoregions in the study area. Mean annual temperature as a limiting factor for the small mammal highlands communities. Species richness increased towards high elevation with an abrupt decrease towards the mountain summit. Environmental factors differentially affect the richness and abundance of small mammals on the elevation gradient.